Special issue: Leveraging agriculture for nutrition in South Asia - Gillespie, Stuart; Bhavani, R. V.; Dangour, Alan D.; Poole, Nigel; van den Bold, Mara (Elsevier, 2019)
This special issue was guest edited by Stuart Gillespie, RV Bhavani, Alan Dangour, Nigel Poole and Mara van den Bold.